ANALISIS KEBUTUHAN RAK FILE DOKUMEN REKAM MEDIS DI RUMAH SAKIT SENTRA MEDIKA CIBINONG - Wahyu Permana; Irda Sari (Journal of Innovation Research and Knowledge, 2021)
The increase in the number of new outpatient IGD and inpatient patients at Sentra Medika Cibinong Hospital 2016-2020 reached 11%, the figure shows the increase in health services provided to the community. This will certainly be comparable to the increase in medical record documents and result in fast storage shelvess full, for that there need to be the addition of new storage shelves. The purpose of this study is to find out the needs of medical record document storage racks at Sentra Medika Cibinong Hospital until 2023. Desriptive research methods and data collection through observation and interviews. Population of 20 racks of medical record storage documents with a sample of 100 documents. The result showed the average thickness of medical record documents was 2,388 cm with the filing length is 6.160 cm. Storage rack size: length 440 cm, height 259 cm and width 46 cm. In conclusion, the prediction of storage shelf needs for 2023 as many as 112 double-sided Roll O’Pack racks, the availability of 20 storage shelves currently requires the addition of 92 storage shelve. The addition of medical record document storage and retention of medical record documents is very important so that the condition of the documents is maintained, not easily damaged and neatly accommodated.